Pemberian recombinant Growth Hormone (rGH) dalam Pakan Buatan terhadap Pertumbuhan Ikan kakap putih Lates calcarifer - septy yolanda eka Saputri; Henky Irawan; Aminatul Zahra (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
This study aimed to gain rGH dose for the growth of Asian Seabass This research was conducted from July to September 2020 in Madong Village, Tanjungpinang City, Riau Islands Province. The method used was a completely randomized design (CRD) with 4 treatments and 3 replications, namely K: without rGH, A: 10 mg rGH / kg of feed, B: 12 ​​mg of rGH / kg of feed and C: 14 mg of rGH / kg of feed. The results of the absolute weight parameter study showed the values ​​of K (24.79 ± 3.13 g), A (23.87 ± 1.91 g), B (42.01 ± 1.87 g) and C (41.93 ± 0.99 g). The daily growth rate parameters indicated the values ​​of K (0.59 ± 0.07 g), A (0.57 ± 0.05 g), B (1.00 ± 0.04 g) and C (1.00 ± 0.02 g). This study concludes that the rGH affects the growth of Asian Seabass seed. It can be seen from the best treatment namely the treatment with a dose of rGH 12 mg/kg of feed with an absolute weight parameter value of 42.01 ± 1.87 g and a daily growth rate of 1.00 ± 0.04 g / day.